PEMAKNAAN GENERASI Z TERHADAP PEMBINGKAIAN PEMBERITAAN OVERTOURISM MEDIA BALIPOST JULI-DESEMBER 2024 - Ficka Destriana Putri; Aulia Ratna Putri Madani; Khayla Putri Wiyandi; Maulydia Zia Hapsari (Jurnal Komunikasi & Media Digital, 2026)
This study discusses the phenomenon of overtourism in Bali, which has gained public attention due to increased media coverage of its impact on the environment, culture, and local communities. This study aims to determine the position of Generation Z readers' interpretation of the framing of overtourism reporting in the local media, BaliPost, from July to December 2024. BaliPost's reporting is interesting to study because it illustrates how regional media interpret tourism issues in their own region. This study uses a qualitative approach with Robert N. Entman's framing analysis method to examine BaliPost's framing of the overtourism issue, as well as Stuart Hall's reception analysis to understand how Generation Z interprets the news coverage. The results show that BaliPost frames overtourism as a governance issue that must be addressed through strict regulations, protection of local communities, and sustainable spatial management. In audience reception, the tendency is toward a dominant-hegemonic position and a negotiating position, while no meaning is found in the opposition position. This absence is influenced by the dominance of Balinese cultural influences and Hindu beliefs that emphasize social harmony and life balance.